Social and Cultural Context of Intercultural Counselling - Peavy, R. Vance; Li, Han Z. (Canadian Journal of Counselling and Psychotherapy, 2007)
In this article, we argue for two points. First, successful intercultural counselling depends on how well the counsellor understands the social contextual factors surrounding the interaction. Second, intercultural counselling is a collaborative process, the success of which depends on how well the counsellor and clients coordinate their communication on process and content. Counsellor knowledge of social and cultural contextual variables contributes to common ground with the client. However, it is the counsellor's ability to monitor and attune to the moment-by-moment changes of counselling discourse that contributes most to the success of an intercultural counselling session.